Kolaborasi Pemerintah dan Masyarakat dalam Membangun Ekosistem Kewirausahaan Pariwisata Bahari Berkelanjutan di Negeri Hukurila, Kota Ambon - Akapip, Nindy; Kissya, Vrancisca (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
This article explores the collaboration between the government and the community in building a sustainable marine tourism entrepreneurship ecosystem in Negeri Hukurila, Ambon City. The study aims to examine the roles and synergy between these actors in fostering the development of a local economy based on environmentally friendly and sustainable marine tourism. The research employs a qualitative approach through field observations, in-depth interviews with key stakeholders, and document analysis related to tourism policies and local development. The findings indicate that effective collaboration between the government and the community is crucial for the successful development of the tourism entrepreneurship ecosystem. The government acts as a facilitator by implementing supportive policies, providing entrepreneurship training, and developing infrastructure, while the community actively participates as key actors in businesses leveraging local potential, such as beach tourism, ecotourism, and creative products derived from marine resources. Challenges include limited resources, community capacity constraints, and environmental degradation threats. However, intensive and trust-based collaboration has proven to enhance the competitiveness of the tourism ecosystem in the region. The novelty of this study lies in identifying an adaptive and participatory collaboration model that can serve as a reference for developing tourism entrepreneurship ecosystems in other coastal areas. The study recommends strengthening community capacity, diversifying businesses based on local potential, and applying sustainable tourism principles to preserve the environment and improve local community welfare.